Assessment of Recent Knowledge, Attitude, and Practice Towards Antimicrobial Resistance and Their Consumption During COVID-19 in Balochistan - Mumtaz, Fatima; Summan, Mah Gul; Kalsoom, Aasia; Altaf, Awais; Shabbir, Ghulam (Biological and Clinical Sciences Research Journal, 2025)
Antimicrobial resistance is one of the biggest problems across the world. This condition threatens the effectiveness of treatments against infectious diseases. Most people are less aware of the causes of antimicrobial resistance. The irrational use of antibiotics during the COVID era has further aggravated the situation. In the current study, the recent knowledge, attitudes, and practices related to antibiotic resistance during the COVID-19 era were assessed among the people of Balochistan. Methods: The World Health Organization questionnaire on antimicrobial resistance, with certain modifications, was used in this study. The population was divided into two categories: the general population and healthcare professionals, including doctors, pharmacists, and medical students. The population of each category was sampled randomly among the different districts of Balochistan. The responses to each question were recorded and statistically analyzed to evaluate the significance of knowledge about antimicrobial resistance. Results: A total of 250 questionnaires' responses, consisting of males 103 (41.2%) and females 147 (58.8%), were analyzed in this study. Most of the participants (69.8%) were familiar with the term "antibiotic resistance. 57.6% of respondents agreed that improper use of antibiotics causes resistance in microbes. Only 33.2% of people expressed concern that antibiotic resistance was one of the major issues worldwide. The percentage of self-medication was found to be 26.6%. Our study also showed a correlation between education level and knowledge of antibiotic resistance. The overall mean knowledge score in our study was 3.67. Conclusion: Our findings suggest that the people of Balochistan lack knowledge about antimicrobial resistance. Their attitude and practices toward the usage of antibiotics were not promising. There is a need to raise awareness among the public about the responsible use of antibiotics and the issue of antibiotic resistance. Our study also indicated a danger-related increase in antibiotic resistance due to the overuse of antibiotics during the COVID period.